Faking the Desire to Learn - Dompnier, Benoît; Darnon, Céline; Butera, Fabrizio (Psychological Science, 2009)
Research on achievement goals has demonstrated that mastery goals positively impact achievement-related outcomes, but paradoxically hold an inconsistent relation with academic achievement. We hypothesized that this relationship depends on the reason why students endorse mastery goals—namely, to garner teachers' appreciation (social desirability) or to succeed at university (social utility). First-year psychology students completed a mastery-goal scale in a standard format, with social-desirability instructions and social-utility instructions. Participants' grades on academic exams were recorded later in the semester. Results indicated that students' perceptions of both social desirability and social utility related to mastery goals moderated the relationship between the endorsement of mastery goals and final grades. This relationship was reduced by the increase of perceived social desirability of mastery goals, and strengthened by the increase of perceived social utility of these goals.